Features of the state of neuro-endocrine factors of adaptation under different options of uric acid metabolism in healthy female rats - Popovych, Igor; Bombushkar, Igor; Badiuk, Nataliya; Korda, Inna; Zukow, Walery; Gozhenko, Anatoliy (Journal of Education, Health and Sport, 2020)
Background. As part of the project "Physiological activity of uric acid", we previously identified 4 variants-clusters of uricemia and uricosuria both in rats and in humans. It was shown that the clusters differ from each other in the constellation of immunity parameters, which to one degree or another correlate with uricemia and uricosuria. The aim of this study was to identify autonomic and endocrine adaptogenic factors, the combination of which differentiates previously formed quantitative and qualitative variants of uric acid metabolism in rats. Materials and Methods. Experiment was performed on 58 healthy female Wistar rats 220-300 g. The serum and urine levels of the uric acid, calcium, phosphates, sodium and potassium were determined. The neuro-endocrine status evaluated by the HRV parameters; serum levels of the hormones such as corticosterone, triiodothyronine and testosterone; daily excretion of 17-ketosteroides; electrolytes markers of mineralocorticoid, parathyroid and calcitonin activities as well as by the thickness of glomerular, fascicular, reticular and medullar zones of the adrenals. Results. The previously identified four variants-clusters of uric acid metabolism differ from each other by a constellation of 10 neuro-endocrine adaptation factors that reflect the state of glucocorticoid, androgenic and catecholamine functions of the adrenal glands, as well as HRV-marker of vagal tone and electrolyte markers of sympatho-vagal balance as well as calcitonin and parathyroid activities. Classification accuracy is 90%. Uricosuria and uricemia are negatively correlated with HRV-markers of sympathetic tone and circulating catecholamines, the level of corticosterone and the thickness of the fascicular zone of the adrenal cortex secreting them, as well as the level of triiodothyronine and the Ca-P marker of calcitonin activity, on the other hand, they are positively correlated with the HRV marker of vagal tone and urinary excretion of 17-ketosteroids. The rate of determination of neuro-endocrine adaptation factors by uric acid is 62%. Conclusion. Uric acid is naturally associated with the state of autonomous and endocrine adaptation factors in healthy female rats.